Direct and Residual Effect of FYM and Zinc Levels on Yield, Zn Uptake and Available Zn in Rice-Wheat Sequence on a Vertisol - R.S. Khamparia, P.S. Kulhare, G.D. Sharma, B.L. Sharma and (Journal of the Indian Society of Soil Science, 2015)
A field experiment was conducted on a Vertisol at research farm of Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur to study the effect of different levels of farmyard manure (FYM) (0, 2.5, 5 and 10 t ha-1) and zinc (Zn) (0, 2.5, 5 and 10 kg ha-1) in rice variety JR 201 and wheat variety GW 273 in rice-wheat cropping sequence during 2003-04 to 2006-07. The FYM levels were applied to rice crop during 2003, 2005 and 2006. The Zn levels were applied only once to first rice crop during 2003. The residual effect of FYM and Zn levels was observed in succeeding wheat and rice crops. Application of 5 and 10 t FYM ha-1 and its residual effect, in general, significantly increased the grain yield of rice, Zn uptake by rice and wheat, and available Zn in post-harvest soils after rice and wheat over control. However, the residual effect of 10 t FYM ha-1 significantly increased the wheat grain yield over control. Application of 5 and 10 kg Zn ha-1 and its residual effect significantly increased the rice grain yield for two and four year, respectively and Zn uptake by rice and wheat as well as post-harvest available Zn after rice and wheat over control during all the years. The residual effect of 10 kg Zn ha-1 significantly increased the wheat grain yield over control for four years. The interaction between FYM and Zn levels was found to be non-significant for yield, Zn uptake by rice and wheat and available Zn after harvest of rice and wheat.